Penerapan Root Assessment Method dan Pembobotan ROC untuk Evaluasi Kinerja Tim Penjualan - Yudhistira, Aditia; Wahyudi, Agung Deni; Nuryaman, Yosep (PT. SNN MEDIA TECH PRESS, 2024)
The performance of the sales team is one of the important indicators of a company's success, which is measured through the achievement of sales targets, negotiation skills, and efficiency in managing customer relationships. Problems in the appraisal of sales team performance often arise due to various factors that affect objectivity and fairness in evaluation. One of the main problems is the lack of consistent assessment standards, where each team member may be assessed with different assessment opinions, leading to bias in evaluation results. The application of the Root Assessment Method and ROC Weighting in the performance evaluation of the sales team is an innovative and effective approach to improve productivity and team performance. The combination of these two methods not only facilitates in-depth analysis of individual and team performance, but also supports strategic decision-making in the continuous development and improvement of sales team capabilities. The results of the sales team's performance evaluation assessment ranking, Team J ranked first with a final score of 4.3981, showing the most superior performance among the entire team. In second place, Team G obtained a score of 4.388, followed by Team D in third place with a score of 4.3752. These results provide a comprehensive picture of each team's performance rankings, with Team J showing top performance, while Team F needs further improvement.